Sarco/Endoplasmic Reticulum Calcium ATPase Inhibitors: Beyond Anticancer Perspective - Peterková, Lucie; Kmoníčková, Eva; Ruml, Tomáš; Rimpelová, Silvie (Journal of medicinal chemistry, 2020)
The sarco/endoplasmic reticulum calcium ATPase (SERCA), which plays a key role in the maintenance of Ca2+ ion homeostasis, is an extensively studied enzyme, the inhibition of which has a considerable impact on cell life and death decision. To date, several SERCA inhibitors have been thoroughly studied and the most notable one, a derivative of the sesquiterpene lactone thapsigargin, is gradually approaching a clinical application. Meanwhile, new compounds with SERCA-inhibiting properties of natural, synthetic, or semisynthetic origin are being discovered and/or developed; some of these might also be suitable for the development of new drugs with improved performance. This review brings an up-to-date comprehensive overview of recently discovered compounds with the potential of SERCA inhibition, discusses their mechanism of action, and highlights their potential clinical applications, such as cancer treatment.
Keywords: zvířata; Animals; Protein Structure, Secondary; sekundární struktura proteinů; Humans; Gene Regulatory Networks; protinádorové látky; Enzyme Inhibitors; Neoplasms; Antineoplastic Agents; nádory; genové regulační sítě; Sarcoplasmic Reticulum Calcium-Transporting ATPases; sarkoplazmatická Ca2+-ATPáza; lidé; inhibitory enzymů